Paradigma Baru Pengembangan Wakaf Produktif (Kajian Empiris Badan Wakaf Indonesia Propinsi Bangka Belitung) - Wulpiah, Wulpiah (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2019)
At present the study and concern of the muslim community is being focused on socializing, utilizing and developing waqf, especially productive waqf. Which is one of the instrument of sharia social finance. Event the existence of productive endowments is very potential which is allegedly one of the complentary instrument solution for development financing.There are many form of development and utilization of productive waqt in Indonesia both in the fields of agriculture plantations, economics such as establishment of sharia hotel, health; establishment of hospital, infrastructure and other business centers. Cash waqf which is one element of productive endowment can be alternative way of “expansion” of development and development of Islamic economic which can ultimately strengthen financial system stability.The focus this paper will be “reading” the direction of development of productive waqf carried out by BWI Bangka Belitung regarding of socializing, education and implementation program. Therefore, “built in” the new paradigm of productive waqf so that its management its carried out professionally must continue to be encouraged. Furthermore, the intended paradigm is increasing capacity of nadzir; besides having religious knowledge and trust and also having enterpreneursip spriit. Bisides that BWI Bangka Belitung must start introducing cash waqf.